Associations Between PTSD Symptom Custers and Longitudinal Changes in Suicidal Ideation: Comparison Between 4-Factor and 7-Factor Models of DSM-5 PTSD Symptoms - Chu, Che-Sheng; Chou, Po-Han; Wang, Shao-Cheng; Horikoshi, Masaru; Ito, Masaya (Frontiers in Psychiatry, 2021)
Objective: The association between posttraumatic stress disorder (PTSD) and suicidal ideation (SI) is well known. However, few studies have investigated the associations between PTSD cluster symptoms based on the fifth edition of the Diagnostic and Statistical Manual for Mental Disorders (DSM-5) and changes in suicide risk longitudinally. Methods We adopted a longitudinal study design using data from the National Survey for Stress and Health of 3090 Japanese population. The first and second surveys were conducted on November 2016 and March 2017, respectively. The suicidal ideation attributes scale was applied to assesses the severity of suicidal ideation at baseline and the follow-up period. A multivariate linear regression model was conducted to examine the associations between 4- or 7-factor model of PTSD symptom clusters at baseline and longitudinal changes in SI. Results: Overall, 3090 subjects were analyzed (mean age, 44.9 ± 10.9 years; 48.8% female) at baseline and 2163 completed the second survey. In the 4-factor model, we found severity of negative alternations in cognition and mood were significant associated with increased SI after 4 months. In the 7-factor model, we found severity of anhedonia and externalizing behavior at baseline were significantly associated with increased SI during the follow-up period. Conclusions: We found the 7-factor model of DSM-5 PTSD symptoms may provide greater speciﬁcity in predicting longitudinal SI change in the general population. Closely monitoring specific core PTSD symptoms may be more effective in mitigating key clinical and functional outcomes.